Incorporating seller/buyer reputation-based system in blockchain-enabled emission trading application - Khaqqi, Khamila Nurul (2019)
Emission Trading Scheme (ETS) has dual aims to reduce emission production and stimulate adoption of long-term abatement technology. Whilst it has generally achieved its fi rst aim, its issues are hindering the accomplishment of the second. Several solutions have been proposed to improve ETS's efficacy, yet none of them have considered the advancement of Industry 4.0. This paper proposes a novel ETS model customised for Industry 4.0 integration. It incorporates blockchain technology to address ETS's management and fraud issues whilst it utilizes a reputation system in a new approach to improve ETS efficacy. Specifi c design of how the blockchain technology and reputation system are used to achieve these objectives is showed within this paper. The case study demonstrates the inner working of reputation-based trading system-in which reputation signifi es participants performance and commitment toward emission reduction effort. Multi-criteria analysis is used to evaluate the proposed scheme against conventional ETS model. The result shows that the proposed model is a feasible scheme and that the benefi ts of its implementation will outweigh its drawback.